Effect of combined therapies including nutrition and physical exercise in advanced cancer patients: A pooled analysis - Storck, Lena J.; Uster, Alexandra; Gafner, Lucia; Ruehlin, Maya; Gaeumann, Sabine; Gisi, David; Schmocker, Martina; Meffert, Peter J.; Imoberdorf, Reinhard; Pless, Miklos; Ballmer, Peter E. (Frontiers in Nutrition, 2023)
Malnutrition in cancer patients is a complex problem and requires a multimodal approach. Pooled data from two multimodal trials were analyzed regarding nutritional status and survival time. Data from two trials with advanced cancer patients were included and in both trials, patients in the intervention group received at least three times nutritional counseling and supervised training sessions. Patients in the control group continued being treated according to usual care. Nutritional status was measured using BMI, body composition and handgrip strength. Survival time was analyzed using the Cox proportional hazard model with the period between beginning of the trial and death as underlying time scale. 68 men (61.8%) and 42 women (38.2%) were randomized either to the intervention (n = 56) or the control (n = 54) group. The inter-group difference for changes in BMI and body composition were not statistically significant after three months. Handgrip strength improved significantly from 34.4 ± 10.2 kg to 36.3 ± 9.9 kg at three months in the intervention compared to 33.9 ± 9.2 kg to 34.9 ± 9.1 kg in the control group (p = 0.006), though. The analysis of survival time showed no inter-group difference for all patients. A detailed analysis for different diagnoses showed that in patients with lung cancer, the covariates "CRP value", "days from first diagnosis to randomization" as well as "gender" were significantly associated with survival time. Patients with higher CRP value had a shorter survival time and female patients had a shorter survival time than male patients in our analysis. In addition, patients with pancreatic cancer randomized to the control group had a 20% shorter survival time than those in the intervention group (p = 0.048). The pooled analysis showed a significant improvement of handgrip strength in advanced cancer patients through the implementation of a multimodal therapy. Handgrip strength is of prognostic significance in hospitalized patients due to its association with mortality and morbidity. However, no improvements in further tests were observed. There is great need for further investigations examining the effect of nutritional and exercise therapy on survival time with focus on different cancer diagnoses.